Métamorphoses de l’idée d’empire à la Renaissance - Thierry Ménissier (Astérion)
During the Renaissance, as an age of transition, the political idea of empire (a legacy of the Middle Ages) is subject to a series of evolutions leading to the modern reality of a large market, gradually coordinating national economies and their influence networks. Do these evolutions allow us to speak of an « economical version of the empire » ? Can we view this process, described through the geopolitical relationships of the Renaissance, as a prefiguration of modern globalization ? This paper deals with these questions from various points of view, in order to prove that the Renaissance idea of empire undergoes « metamorphosis », or evolutions, which modify its concept, regarding notably the relationship between domination and territoriality.